2011
DOI: 10.1039/c0dt01148g
|View full text |Cite
|
Sign up to set email alerts
|

Strong agostic-type interactions in ruthenium benzylidene complexes containing 7-azaindole based scorpionate ligands

Abstract: . (2011). Strong agostic-type interactions in ruthenium benzylidene complexes containing 7-azaindole based scorpionate ligands. Dalton Transactions, 40 (4), 951-958.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 102 publications
3
17
0
Order By: Relevance
“…Unfortunately, this means that the one‐bond B–H coupling constant could not be determined from the boron‐coupled experiment. An increased linewidth of the boron signal is typical in complexes of this type and has previously been observed in other complexes containing aryl‐substituted ligands 4a,11c,11d. The 31 P{ 1 H} NMR spectra of 4 – 6 show singlet resonances between δ = 66.3 and 68.8 ppm.…”
Section: Resultssupporting
confidence: 67%
See 3 more Smart Citations
“…Unfortunately, this means that the one‐bond B–H coupling constant could not be determined from the boron‐coupled experiment. An increased linewidth of the boron signal is typical in complexes of this type and has previously been observed in other complexes containing aryl‐substituted ligands 4a,11c,11d. The 31 P{ 1 H} NMR spectra of 4 – 6 show singlet resonances between δ = 66.3 and 68.8 ppm.…”
Section: Resultssupporting
confidence: 67%
“…We recently reported the benzylidene–ruthenium complexes [RuCl{κ 3 ‐ NNH ‐R(H)B(azaindolyl) 2 }{=C(H)Ph}(PCy 3 )] [R = azaindolyl ( 1 ), phenyl ( 2 )] and [RuCl{κ 3 ‐ NNH ‐HB(azaindolyl) 3 }{PCy 2 (C 6 H 9 )}(PCy 3 )] ( 3 ; Figure 4). 11c Within these complexes very strong interactions were observed between the ruthenium centre and the borohydride units, as confirmed by their spectroscopic and structural characterisation (Table 1). A comparison of these compounds and other literature examples revealed that such interactions are particularly strong in those cases in which the borohydride unit is located trans to a halide or similar π‐donor ligand 11c.…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…8). 23 The unusual rearrangement affording the complex [CpRu{(Z 3 -CH 2 C(CH 2 ) 3 CCH 2 PCy 2 (Z 2 -C 6 H 9 )] + (21) resulted from the addition of 1,6-heptadiyne to [CpRu(NCCH 3 ) 2 (PCy 3 )] + (19) through an intermediate allyl carbene 20. 24 In this system, the phosphonium ligand is coordinated to the metal centre through the CQC double bond at the a position of the phosphorus, which is not bound to the ruthenium (Fig.…”
Section: B Tricyclohexylphosphine Complexesmentioning
confidence: 99%